Dengue vector surveillance in major towns of Malaysia - Chen, Chen Dhang; Wan-Norafikah Othman,; Lau, Koon Weng; Chin, Ai Chdon; Lee, Han Lim; Chew, Fong Peng; Mohd Sofian-Azirun, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
Ovitrap surveillance was conducted between February and June 2017 to determine the abundance and distribution of dengue vectors in 13 residential areas located in major towns of different states in Malaysia. Forty ovitraps were placed randomly within the vicinity of buildings which were protected from sunlight and rain. The study revealed that ovitrap index (OI) ranged from 12.50% to 87.50% across all study sites. Both Aedes aegypti and Aedes albopictus were found breeding in all study sites except for the study sites in Alor Setar, Kedah Gambang, Pahang and Kuala Terengganu, Terengganu, Malaysia in which only Ae. albopictus was recorded. The mean number of larvae obtained revealed that Ae. albopictus was a more dominant dengue vector as compared to the mean number of Ae. aegypti larvae in nine out of thirteen study sites (P<0.05). Mixed breeding of both Aedes species were found in 4.00% to 28.57% of the total number of recovered ovitraps from all study sites. This study revealed that OIs obtained from all these major towns were >10%, indicating Malaysia is generally at risk of dengue outbreak, and control approaches must be carried out immediately to reduce the vector population to a level below the threshold of transmission.